Computational Fluid Dynamic (CFD) for Microchannel Microfluidic Devices - Mohd Fairuz Harun (Universiti Malaysia Perlis (UniMAP), 2008)
Microfluidic devices have been developing rapidly since the concept of fluid-integrated-circuits, lab-on-a-chip or micro-total-analysis systems (uTAS) was introduced. Among the great benefits of miniaturized devices are that they require less fabrication material and can also be manufactured as cheap disposable test kits. They consume smaller amounts of expensive reagents in comparison to conventional macro-scale devices and can control temperature and other system properties precisely. Miniaturized systems can increase yields significantly in chemical, engineering, biological and clinical applications and can also reduce process time. More importantly, micro-devices can have additional functionalities beyond those of conventional devices, with the potential to revolutionize many scientific areas and associated industries. The design, fabrication and application in microfluidics has attracted researchers from a variety of disciplines including chemistry, biology, physics, engineering and applied mathematics. This report focused on laminar flow which is the definitive characteristic of microfluidics. Fluids flowing in channels with dimensions on the order of certain micron size and at readily achievable flow speeds are characterized by low Reynolds number, Re as described in introduction, flows in this regime are laminar, not turbulent: The surfaces of constant flow speed are smooth over the typical dimension of the system, and random fluctuations of the flow in time are absent. In the long, narrow geometries of microchannels, flows are also predominantly uniaxial: The entire fluid moves parallel to the local orientation of the walls. The significance of uniaxial laminar flow is that all transport of momentum, mass, and heat in the direction normal to the flow is left to molecular mechanisms: molecular viscosity, molecular diffusivity, and thermal conductivity.